The use of Electronic Medical Record (EMR) in hospitals during the COVID-19 pandemic in Indonesia: a systematic literature review - Paramesthi, Prasasya; Jati, Sutopo Patria; Suryoputro, Antono (BKM Public Health and Community Medicine, 2024)
Purpose: Electronic medical records (EMR) are information technology-based systems that store and manage patient medical data. EMR are beneficial for improving healthcare services' efficiency, effectiveness, and security. The COVID-19 pandemic has driven the adoption of EMR, but there are still challenges, such as the surge in patient numbers and problems with EMR filling. This study aimed to investigate the use of EMR in hospitals during the COVID-19 pandemic in Indonesia. Method: This study was a systematic literature review using the PRISMA diagram. Article search was conducted based on the PICO model eligibility criteria. The articles used were retrieved from 3 databases: Google Scholar, ResearchGate, and Cerdika. The researcher limited the publication year of the journals to 2020-2021, when the COVID-19 pandemic was ongoing, and added the keyword "COVID-19" to the journals published in 2022-2023. Results: The results of the study showed that the COVID-19 pandemic has had a significant impact and the need for the implementation of EMR due to its various benefits, such as improving the efficiency and effectiveness of healthcare services, facilitating access to patient health information, increasing collaboration among healthcare workers, accelerating the process of clinical decision-making, and improving the security and accuracy of health data. However, implementing EMR during the COVID-19 pandemic has only sometimes been smooth. Some challenges include suboptimal infrastructure, untrained human resources, and inadequate policies. Conclusion: To overcome these challenges, efforts from various parties, including the government, hospitals, and healthcare workers, are needed.